The Effect of Profitability Ratio, Leverage Ratio, Liquidity Ratio and Activity Ratio on Stock Return with Inflation As A Moderating Variable (Study on Stocks of Companies Actively Listed in LQ-45 in The Indonesia Stock Exchange (IDX) for The Period 2018-2022) - Sholikhah, Mar'ah; Kartadjumena, Eriana (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze company performance against stock returns in Companies actively listed in LQ-45 on the Indonesia Stock Exchange (IDX) in 2018 to 2022. Company performance consists of profitability ratios proxied by return on assets, leverage ratios proxied by debt to equity ratio, liquidity ratio proxied by current ratio and activity ratio proxied by total assets turnover and macroeconomic variables, namely inflation as a moderating variable. Data were collected from the Indonesia Stock Exchange website and the websites of each related company. The research method used is a descriptive and verification method with a quantitative approach. The population in this study is the financial statements of 23 companies listed actively in the LQ-45 on the Indonesia Stock Exchange (IDX) in 2018 to 2022 (5 years), namely 115 financial statements that meet the criteria. The analysis method used is panel data regression analysis and Moderate Regression Analysis (MRA). The results of the study show that the profitability ratio (ROA) and leverage ratio (DER) have a negative effect on stock returns. While the liquidity ratio (CR) and activity ratio (TATO) have a significant positive effect on stock returns. The results of this study also show that inflation cannot moderate the effect of the profitability ratio, leverage ratio, liquidity ratio and activity ratio on stock returns.